Strategic Faults in Implementation of Hospital Accreditation Programs in Developing Countries: Reflections on the Iranian Experience - Aidin Aryankhesal (Kerman University of Medical Sciences, 2016)
Establishment of hospital accreditation programs is increasingly growing across numerous developing nations. Such initiatives aim to improve quality of care. However, such establishments, mainly incentivized by successful and famous accreditation plans in developed countries, usually suffer from lack of necessary arrangements which, in turn, result in undesired consequences. Indeed, the first priority for such nations, including Iran, is not establishment of accreditation programs, yet strict licensing plans.